Legal Construction of Nationalism and National Identity in The Hashemite Kingdom of Jordan - Siyam, Zaina (AUC Knowledge Fountain, 2021)
Nationalism is an ideology that is not unique to one nation or one area, but it is a concept unique in the way it is defined. How it is defined and what it really is depends on where the definition is coming from. It is most important to post-colonial nations that relied and still rely on the creation of national identity and construction of an imagined community, in order to reach their liberation. Nations are imagined communities constructed through shared history, beliefs, traditions, and experiences that happen over different periods in time, between individuals that do not necessarily know each other on a face-to-face basis, nationalism is the ideology that brings all the shared elements together and creates a desire to belong, and national identity is the result of those social constructs. Then, in order to maintain the nation, law is used as a tool to protect a nation’s sovereignty and the dominance of a certain national identity. However, the relationship between law and nationalism and national identity is not one-sided. Law does not only help maintain and reinforce national identity but law is also influenced by nationalism and the most prominent national identity in the territory. The Hashemite Kingdom of Jordan is no stranger to the nation-building process and is heavily reliant on the existence of a Jordanian national identity in order to remain powerful. The Jordanian nation has carried out processes of Jordanization throughout the years in order to keep its population made up of real Jordanians, but there is a long history between real Jordanians and their Palestinian neighbors.